IMPLEMENTASI STRATEGI PEMASARAN MELALUI SOCIAL MEDIA MARKETING PADA UMKM CV BERKAT TANI - Fitriana Aidnilla Sinambela; Rizni Aulia Qadri; Jeffry Kurniawan; Rensia Ester Herdinasari; Bastanta Sebayang; Lutfy Setia Wahyudi Haqiqi Ali (Juremi: Jurnal Riset Ekonomi, 2023)
This study discusses how to optimize marketing through social media at CV Berkat Tani SMEs. Currently, CV Berkat Tani is facing fierce competition from other MSMEs selling similar products. This obstacle was factored in by the owner's lack of understanding of the latest business strategy developments which caused CV Berkat Tani to have little engagement from target consumers and a brand image that had not yet been formed. So this study aims to provide an understanding regarding good Social Media Marketing strategies for UMKM CV Berkat Tani and help optimize the use of social media and online platforms to build a more effective and attractive Brand Image and increase promotion using digital tools that guarantee increased engagement. The method used is descriptive qualitative analysis which is collected through interviews with the owner, surveys through questionnaires and observations which then analyze the appropriate strategy. The results obtained are that UMKM CV Blessing Tani has a good brand image and the number of followers on the Instagram account CV Blessing Tani has increased from before, which was 250 followers. In addition, the number of Profile Visits on the Sugarbelly Instagram account has also increased, reaching 50 visitors in the last 10 days